Kinetics investigation of phenolic pollutant degradation via Serratia marcescens ABHI 001 and its application in wastewater treatment - Singh T.; Srivastava N.; Teklemariam A.D.; Mishra P.K.; Almuhayawi M.S.; Haque S.; Harakeh S.; Pal D.B.; Gupta V.K. (My University, 2025)
In the present work, kinetic study has been conducted in order to effectively eliminate the p-cresol from wastewater employing isolated bacterial strain Serratia marcescens ABHI001 under batch shake flasks in the concentration varying from 50 to 500 mg/L. Further, effects of various parameters including p-cresol concentration, inoculum dosage, temperature, pH and agitation have been investigated. It was found that 10% v/v inoculum of 24 h age, was effective in degrading p-cresol. Beside this, it was noticed that the concentration of P-cresol above 100 mg/L exhibited an inhibitory effect. The maximum specific growth rate (μmax) was obtained to be 0.360 h−1 for 100 mgL−1 concentration. Further, the experimental results were well fitted with Halden's and Andrew's models and kinetic parameters μmax, KS and Ki in case of Haldane model were calculated to be 0.9697 h−1, 88.07 mgL−1 and 219.9 mgL−1, respectively whereas the corresponding values in case of Andrews's constants were 0.6917 h−1, 62.83 mgL−1 and 307.4 mgL−1, respectively. The yield coefficient for the growth on p-cresol was found to be 0.82. © 2022 Elsevier Ltd